Pembuatan Mortar Polimer Nanokomposit Sebagai Bahan Perbaikan - Zuul Fitriana Umari; Ayu Marlina (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Construction in the field can often be encountered with various problems, one of which is damage to concrete structures or non-concrete structures that can affect the weakening of a structure. Many developed countries have carried out polymer mortar development efforts. Until now, the development of polymer mortar is still ongoing to reduce the use of cement and anticipate global warming. One of them is by utilizing polymer as an adhesive substitute for cement so that a strong mortar is produced in a shorter time. This research combines 40%-55% epoxy resin and hardener, 40% fine aggregate, 5%-20% Fly Ash and 1%-5% nanosilica. The results obtained show that the initial bond setting time is 70 minutes and the final bond is 110 minutes. This result is faster than normal mortar. The more epoxy used, the longer the bonding time. For Compressive strength test maximum Theobtained were results62 MPh with a mixture of 38% epoxy and hardener, aggregate 40% fine, 20% fly ash and 2% nanosilica. For specific gravity, the result is 1,760 Kg/M3. Aggregates and fly ash with fine grains can produce higher mechanical strength as fillers coupled with nanosilica which can increase strength, the more nanosilica used , the strength of the nanocomposite material increases to appoint critical and then decreases. Keywords: Polymer Concrete, Fly Ash and Nanocomposites